STABILITY ASSESSMENT OF AN AGING EARTH FILL DAM CONSIDERING ANISOTROPIC BEHAVIOUR OF CLAY (GEOMATE Journal, 2020)
Anisotropic behaviour of the clay core, blanket, and foundation of aging water retaining earth fill dams on glacio-lacustrine clay deposits in Canada may be a result of environmental loading. The repeated wetting-drying and freezing-thawing cycles produce fissures that can cause degradation of strength with time. Undisturbed clay samples taken from field investigations of an existing aging water retaining earth fill damwere tested in the laboratory to obtain the parameters used in the numerical modeling. A testing program was implemented in order to determine the basic soil properties along with mineralogy, strength, and deformation characteristics of the collected clay samples. Laboratory tests include index property tests, Scanning Electron Microscopy (SEM) tests, X-Ray Diffraction (XRD) tests, one-dimensional consolidation oedometer tests, consolidated drained direct shear tests, and isotropically consolidated undrained triaxial compression tests.Results revealed that the clay samples from the clay core, blanket and foundation were similar in terms of structural and mineralogical composition. The observed interlayered smectite and illite indicated that the micro fabric was anisotropic. Strength anisotropy was noticed as results had different cross shear and horizontal shear strength values. Numerical modeling was performed to assess the slope stability of an aging earth dam that experienced sliding movements using parameters from the completed laboratory investigation. Findings from slope stability analyses indicated that a better representation of the observed site conditions was evident when strength anisotropy was considered.